Compressive failure analysis for low length-width ratio composite laminates with embedded delamination. (September 2018) - Zhao, Libin; Liu, Yaling; Hong, Haiming; Wang, Kangkang; Zhao, Jie
Abstract: For low length-width ratio composite laminates with embedded delamination under compressive loading, different failure modes occur and interact tightly, which catastrophically decrease the load carrying capacity of the laminates. In order to systematically investigate the compressive behaviour of these laminates, a thorough progressive failure model taking into account the interaction among intralaminar failure, interlaminar failure and buckling failure was established. In this model, the intralaminar failure was evaluated with the progressive damage method (PDM), and the interlaminar delamination growth was simulated with the virtual crack closure technique (VCCT). Compression tests of low length-width ratio composite laminates with different embedded circular delaminations were conducted. Good agreements between numerical predictions and experimental results, including failure loads, load-central deflection curves and shapes of delamination growth, were obtained. It follows that under compressive loading, low length-width ratio laminates with small embedded delamination fail due to the buckling and intralaminar failure, while more severe laminate failure is induced by the buckling, intralaminar failure and additional delamination growth for low length-width ratio laminates with large embedded delamination. Highlights: Low length-width ratio laminates with delamination under compression was explored. A progressive failure model was established to examine different failure modes. Large delamination diameter in the laminates leads to additional delamination growth.